Supporting First Nations Family Caregivers and Providers: Family Caregivers’, Health and Community Providers’, and Leaders’ Recommendations - Amber Ward; Laurie Buffalo; Colleen McDonald; Tanya L’Heureux; Lesley Charles; Cheryl Pollard; Peter G. Tian; Sharon Anderson; Jasneet Parmar (Diseases, 2023)
Family caregivers and care providers are increasingly becoming more distressed and reaching a breaking point within current systems of care. First Nations family caregivers and the health and community providers employed in First Nations communities have to cope with colonial, discriminatory practices that have caused intergenerational trauma and a myriad of siloed, disconnected, and difficult-to-navigate federal-, provincial/territorial-, and community-level policies and programs. Indigenous participants in Alberta’s Health Advisory Councils described Indigenous family caregivers as having more difficulty accessing support than other Alberta caregivers. In this article, we report on family caregivers’, providers’, and leaders’ recommendations to support First Nations family caregivers and the health and community providers employed in First Nations. We used participatory action research methods in which we drew on Etuaptmumk (the understanding that being in the world is the gift of multiple perspectives) and that Indigenous and non-Indigenous views are complementary. Participants were from two First Nation communities in Alberta and included family caregivers (n = 6), health and community providers (n = 14), and healthcare and community leaders (n = 6). Participants advised that family caregivers needed four types of support: (1) recognize the family caregivers’ role and work; (2) enhance navigation and timely access to services, (3) improve home care support and respite, and (4) provide culturally safe care. Participants had four recommendations to support providers: (1) support community providers’ health and wellbeing; (2) recruit and retain health and community providers; (3) improve orientation for new providers; and (4) offer providers a comprehensive grounding in cultural awareness. While creating a program or department for family caregivers may be tempting to address caregivers’ immediate needs, improving the health of First Nations family caregivers requires a population-based public health approach ...